Development of problem-based learning based on multimedia to improve learning outcomes - Ade Hermansyah Pohan; Samsidar Tanjung; Restu Restu (Himpunan Pengembang Kurikulum Indonesia, 2025)
Implementing the integrated science and social studies subject (IPAS) faces several challenges, including limited teacher understanding of the integrative concept and inadequate learning resources. This study aims to develop interactive multimedia based on Problem-Based Learning (PBL) to improve IPAS learning outcomes in V-grade elementary school students. This study used the 4D development model (Define, Design, Develop, Disseminate). During validation, the developed multimedia was rated highly feasible by media, design, and content experts. Practicality testing showed a usage categorized as very practical. Effectiveness testing indicated that of students experienced a high level of improvement, while some of them showed moderate gains based on N-gain scores. The multimedia enhanced students’ conceptual understanding, critical thinking, creativity, and active engagement in learning. Its development was aligned with constructivist principles and Vygotsky’s Zone of Proximal Development (ZPD), emphasizing scaffolding to support student progress. This study recommends interactive multimedia based on Problem-Based Learning (PBL) as an innovative approach to social studies instruction under the Kurikulum Merdeka. It supports the development of 21st-century competencies in students through meaningful and engaging learning experiences that bridge knowledge and real-world application. Abstrak Implementasi mata pelajaran Ilmu Pengetahuan Alam dan Sosial (IPAS) menghadapi berbagai tantangan, seperti keterbatasan pemahaman guru terhadap konsep integratif dan kurangnya sumber belajar yang memadai. Penelitian ini bertujuan untuk mengembangkan multimedia interaktif berbasis Problem Based Learning (PBL) guna meningkatkan hasil belajar IPAS pada peserta didik kelas V sekolah dasar. Penelitian ini menggunakan model pengembangan 4D (Define, Design, Develop, Disseminate). Pada tahap validasi, multimedia yang dikembangkan dinilai sangat layak oleh ahli media, desain, dan materi. Uji praktikalitas menunjukkan tingkat penggunaan dikategorikan sangat praktis. Uji efektivitas menunjukkan peserta didik mengalami peningkatan hasil belajar dalam kategori tinggi, sedangkan beberapa berada pada kategori sedang berdasarkan skor N-gain. Multimedia ini mampu meningkatkan pemahaman konsep, keterampilan berpikir kritis, kreativitas, serta keterlibatan aktif peserta didik dalam pembelajaran. Pengembangannya selaras dengan prinsip konstruktivistik dan konsep Zone of Proximal Development (ZPD) dari Vygotsky, yang menekankan pentingnya scaffolding untuk mendukung perkembangan peserta didik. Penelitian ini merekomendasikan penggunaan multimedia interaktif berbasis Problem-Based Learning (PBL) sebagai inovasi pembelajaran IPS dalam Kurikulum Merdeka. Pendekatan ini mendukung pengembangan kompetensi abad ke-21 melalui pengalaman belajar yang bermakna dan relevan dengan kehidupan nyata. Kata Kunci: hasil belajar; ilmu pengetahuan sosial; multimedia interaktif; pembelajaran berbasis masalah